TRADISI SUNAT RASUL (KHITAN) DI ACEH SINGKIL (STUDI LIVING HADIS DI DESA PEMUKA KABUPATEN ACEH SINGKIL) - Saleh, Muhammad (UIN Sumatera Utara Medan, 2021)
This research is based on the background of a tradition that is carried out before circumcision. Circumcision is an obligation of Islam. Thus, we need to take a look at the history of circumcision from time to time whether the tradition carried out by the people of Aceh Singkil deviates from Islam or not. Because many traditions are on behalf of religious teachings but, at the time of the application process in the real life is very much different from what is done. This research was conducted to see in more detail how the process of tradition carried out by the people of Aceh Singkil clearly and to find out whether the traditions carried out by the local community are in accordance with Islamic law. This research also provides information about the tools used from time to time and the lessons learned from laser circumcision.